Corpos e sensorialidades no cinema marginal de Júlio Bressane - Guimarães, Marcos Valério (2018)
This research sought to make a diachronic approach between the films O anjo nasceu (1969) and Cuidado, Madame (1970, works by the Brazilian Julio Bressane, and the contemporary theory of sensoriality in cinema, developed from the 1990s by authors such as